2023
DOI: 10.3389/fcvm.2023.1208577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial and ventricular remodeling in atrial fibrillation subtype by using speckle tracking echocardiography

Shirui Lu,
Hongyun Liu,
Jie Sun
et al.

Abstract: BackgroundAtrial fibrillation (AF) is associated with cardiac structural and functional remodeling. We investigated the left atrial (LA) and left ventricular (LV) changes in AF subtypes by using two-dimensional echocardiography strain techniques.MethodsThe study population consisted of 102 subjects with sinus rhythm (control group) and 463 patients with AF, among which 284 patients had paroxysmal AF (PAF) and 179 patients had persistent AF (PerAF). A speckle tracking automatic functional imaging software was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Still, this aspect could not be addressed from the present data set. We did not include patients with persistent AF, likely to fall closer to permanent rather than paroxysmal AF, since the total atrial fibrillation burden is associated with progressive LA structural remodeling and a decrease in LA reservoir function [ 28 , 29 ]. We did not have information on antiarrhythmic drugs other than beta-blockers in our data bank, not specifically focused on AF.…”
Section: Discussionmentioning
confidence: 99%
“…Still, this aspect could not be addressed from the present data set. We did not include patients with persistent AF, likely to fall closer to permanent rather than paroxysmal AF, since the total atrial fibrillation burden is associated with progressive LA structural remodeling and a decrease in LA reservoir function [ 28 , 29 ]. We did not have information on antiarrhythmic drugs other than beta-blockers in our data bank, not specifically focused on AF.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with established AF and normal LVEF, GLS was notably impaired during AF compared to sinus rhythm. 6 Additionally, a study found that indexed GLS measured during AF, adjusted for cycle length, significantly correlates with an increased risk of adverse outcomes, outperforming LVEF. 7 However, in a recent study, there was no evidence of systolic ventricular dysfunction based on myocardial strain in patients with idiopathic AF compared to healthy controls.…”
Section: Atrial Fibrillation Myocardial Work Strain Echocardiographymentioning
confidence: 99%
“…GLS has demonstrated predictive value for new‐onset AF across various clinical contexts, including post‐acute myocardial infarction or stroke presentations, 5 as well as within the general population. In patients with established AF and normal LVEF, GLS was notably impaired during AF compared to sinus rhythm 6 . Additionally, a study found that indexed GLS measured during AF, adjusted for cycle length, significantly correlates with an increased risk of adverse outcomes, outperforming LVEF 7 …”
mentioning
confidence: 99%